B Baqir al-Shadr's Economic Thought and the Concept of State Economy in Article 33 of the 1945 Constitution - Nurjamil; Janwari , Yadi; Jubaedah, Dedah (Inovasi Analisis Data, 2024)
This study aims to analyze the role of the state in the economy through the lens of Baqir al-Shadr's economic theory. Article 33 of the 1945 Constitution connects this theory to the state's exercise of control. This literature research method gathers and examines secondary data from books, scientific journals, research findings, and pertinent articles using a qualitative method, followed by a normative analysis. According to Baqir al-Shadr, the research findings indicate that Islamic economics is not considered a scientific discipline but rather the practical application of Islamic sharia principles rooted in religious beliefs and devotion. This includes the promotion of social justice and the acknowledgement of various forms of property ownership. Second, exploitative and uncontrollable human behavior, rather than a lack of natural resources, is the true cause of economic issues. Furthermore, the government's involvement is necessary for the oversight and resolution of economic issues, particularly in ensuring the well-being of the population and achieving social equilibrium. Article 33 of the 1945 Constitution explicitly grants the state the authority to manage natural resources for the benefit of the people. This abstract presents a concise summary of the correlation between Baqir al-Shadr's economic ideology and the notion of state control, specifically in regard to Article 33 of the 1945 Constitution. It also examines the effects of this correlation on economic regulation and society's welfare.